2020
DOI: 10.1186/s13229-020-00321-w
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in attention to social information from childhood to adolescence in autism spectrum disorders: a comparative study

Abstract: Background Elucidating developmental changes in the symptoms of autism spectrum disorder (ASD) is important to support individuals with ASD. However, no report has clarified the developmental changes in attention to social information for a broad age range. The aim of this study was to investigate the developmental changes in attention to social information from early childhood to adolescence in individuals with ASD and typically developed (TD) children. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 73 publications
(114 reference statements)
1
57
0
Order By: Relevance
“…In previous research using Gaze nder to children between the ages of 1 year and 6 months to 2 years and 2 months, the M-CHAT and the xation data of human and geometry (Movie VII and VIII), showed a signi cant correlation [14]. However, it has been known that TD individuals visually xated on geometric images were enhanced with increasing age [8] and the studies using Gaze nder reported the same trend [13,15,19]. One report showed the xation to the human (relative to geometric patterns) gradually decreased in the TD individuals and stabilized after around 5 years of age [15].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In previous research using Gaze nder to children between the ages of 1 year and 6 months to 2 years and 2 months, the M-CHAT and the xation data of human and geometry (Movie VII and VIII), showed a signi cant correlation [14]. However, it has been known that TD individuals visually xated on geometric images were enhanced with increasing age [8] and the studies using Gaze nder reported the same trend [13,15,19]. One report showed the xation to the human (relative to geometric patterns) gradually decreased in the TD individuals and stabilized after around 5 years of age [15].…”
Section: Discussionmentioning
confidence: 89%
“…However, it has been known that TD individuals visually xated on geometric images were enhanced with increasing age [8] and the studies using Gaze nder reported the same trend [13,15,19]. One report showed the xation to the human (relative to geometric patterns) gradually decreased in the TD individuals and stabilized after around 5 years of age [15]. This trend is considered that during very early development TD infants and toddlers are strongly drawn to the human face [27], while TD individuals may become able to alter their attention to non-social stimuli with increasing age.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The interpretable measurements presented in combination with a promising theoretical background, could for example aid in a step by step visual training of social perception, thus objectifying treatment outcomes and contributing to the development of risk assessments (48,64). Given the flexibility of the social scene presentation paradigm and the practicality of eye tracking technique, such trainings could be developed specifically for children, customized for different developmental ages and levels of difficulties (65). This can eventually facilitate the realization of longitudinal studies and monitoring of long-time interventions (66,67).…”
Section: Discussionmentioning
confidence: 99%